O valor probatório do documento eletrônico: análise interdisciplinar entre a arquivologia e o direito - Martins, Rúbia [UNESP] (2015)
The concept of record is a widely analysed theme in the scope of Archivology and Information Science. In Law, this discussion has basically the record as evidence. In the last decades, the material support of these records has been modified, giving way to the digital environment. The change of the records support to the digital media must meet all the requirements of probationary validity of the records which are recorded on paper, such as authenticity, integrity and reliability. This way, from theoretical research, we aim to promote an interdisciplinary approach between Archivology and Law regarding the probationary aspects of record and electronic record. We could prove that, through an interdisciplinary dialogue between Archivology and Law, the conception of what a record and an electronic record are as evidences for both sciences results in the integration of constituent and similar elements and characteristics in the search for a generic concept of record and electronic record.